2021
DOI: 10.1016/j.cegh.2021.100782
|View full text |Cite
|
Sign up to set email alerts
|

Improving tuberculosis treatment success rate through nutrition supplements and counselling: Findings from a pilot intervention in India

Abstract: In India, the estimated incidence of tuberculosis cases for the year 2018 was 2.69 million. According to WHO, it was responsible for 32 deaths/100,000 population. India also faces a dual burden of tuberculosis and malnutrition which represents an alarming situation. With this backdrop, the current study tries to assess the change in weight and BMI among active TB patients in selected intervention and control site. The study also measures the treatment success rate of the patients. This pilot study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
(25 reference statements)
1
2
0
Order By: Relevance
“…5 A nutritional intervention study conducted in central India by Singh et al found that the mean weight for TB patients increased significantly during each food distribution episode. 7 This corresponds with our study finding of a moderately positive correlation between the number of nutritional kits received and weight-BMI gain. The same study found that the treatment success rate was better among the intervention group as compared to the control group.…”
Section: Analysis Of Weight Changes During Tb Treatmentsupporting
confidence: 91%
“…5 A nutritional intervention study conducted in central India by Singh et al found that the mean weight for TB patients increased significantly during each food distribution episode. 7 This corresponds with our study finding of a moderately positive correlation between the number of nutritional kits received and weight-BMI gain. The same study found that the treatment success rate was better among the intervention group as compared to the control group.…”
Section: Analysis Of Weight Changes During Tb Treatmentsupporting
confidence: 91%
“…Although a Cochrane review of randomized trials of nutritional interventions for PWTB did not find evidence of improvement in cure or mortality, quite importantly, the meta-analysis was insufficiently powered [33]. Two non-randomized interventional studies of nutritional interventions in India, with considerably more participants than in all the studies pooled in the Cochrane review, demonstrated significant improvements in treatment success [34,35].…”
Section: Treatment Of Tbmentioning
confidence: 99%
“…The inclusion criteria were 1 : Pulmonary tuberculosis patient population 2 ; Study with intervention design such as RCT, Quasi-experimental and prospective cohort studies 3 ; Studies conducted in the last 10 years; and 4 Title and abstract based on the research question and the results discuss about medication adherence. Next we excluded the studies 1 : pediatric TB patients 2 ; Full text is not available 3 ; duplication of publications; and 4 the study is not in English or Indonesian.Three researchers independently searched and screened article abstracts following the eligibility criteria and search strategy.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%
“…2 In India, the estimated TB cases in 2018 were 2.69 million, and an estimated 32 per 100, 000 population deaths. 3 The research on Riskesdas (the health research report in Indonesia) released in 2018 showed that the number of TB cases was estimated at around 845,000, with a death rate was 35 per 100,000 population. The data also showed that approximately 93,000 people died from TB.…”
Section: Introductionmentioning
confidence: 99%